Youth justice : ideas, policy, practice - Smith, Roger (Routledge, 2014)
Summary: "The exciting new edition of this well-loved textbook offers a fully expanded and revised account and analysis of the youth justice system in the UK, taking into account and fully addressing the significant changes that have taken place since the second edition in 2007. The book maintains its critical analysis of the underlying assumptions and ideas behind youth justice, as well as its policy and practice, laying bare the inadequacies, inconsistencies and injustices of practice in the UK. This edition will offer an important update in light of intervening changes, as reflected in a change of government and shifting patterns of interventions and outcomes. This book will be a resource for youth justice practitioners and essential to students taking courses in youth crime and youth justice"